Ethnolinguistics Of Madurese Herbal Medicine Product Labels On Shopee - Yanti Linarsih; Royyan Julian; Mohammad Tauhed Supratman (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The rapid expansion of digital marketplaces has transformed the distribution and marketing of traditional products, including Madurese herbal medicine (jamu Madura), which is an important element of traditional healing practices in the Madurese community. Despite the increasing presence of Madurese herbal products on e-commerce platforms such as Shopee, limited scholarly attention has been paid to how language is used on product labels to represent cultural identity and local knowledge systems in a digital marketplace environment. This study examines the linguistic elements found on Madurese herbal product labels marketed through the Shopee marketplace and interprets their cultural meanings from an ethnolinguistic perspective. This research employs a qualitative approach based on digital observations of Madurese herbal product labels displayed on Shopee. The data consist of textual elements found on product labels and descriptions, which were analysed through the stages of linguistic identification, categorisation, and cultural interpretation. The findings reveal that linguistic elements on Madurese herbal product labels can be categorised into four major groups: traditional health terminology, geographical identity markers, symbols of tradition, and cultural metaphors. These linguistic forms represent local knowledge associated with traditional healing practices while simultaneously functioning as marketing communication strategies in the digital marketplace. The study demonstrates that product labels in the Shopee marketplace can be understood as cultural texts that mediate the relationship between language, local cultural identity, and contemporary digital economic practices.